(untitled) (Bangladesh Journal of Pharmacology, 2015)
Endometrial cancer is one of the most prevalent gynaecological malignancies where, currently available therapeutic options remain limited. Recently phytochemicals are exploited for their efficiency in cancer therapy. The present study investigates the anti-proliferative effect of fisetin, a flavonoid on human endometrial cancer cells (KLE and Hec1 A). Fisetin (20-100 µM) effectively reduced the viability of Hec1 A and KLE cells and potentially altered the cell population at G2/M stage. Expression levels of the cell cycle proteins (cyclin B1, p-Cdc2, p-Cdc25C, p-Chk1, Chk2, p-ATM, cyclin B1, H2AX, p21 and p27) were analyzed. Fisetin suppressed cyclin B1 expression and caused inactiva-tion of Cdc25C and Cdc2 by increasing their phosphorylation levels and further activated ATM, Chk1 and Chk2. Increased levels of p21 and p27 were observed as well. These results suggest that fisetin induced G2/M cell cycle arrest via inactivating Cdc25c and Cdc2 through activation of ATM, Chk1 and Chk2.